Selection of sampling step for correlation analysis of cyclostationary processes - Yuzefovych, Roman (Видавництво Львівської політехніки, 2012)
The investigation results of estimators properties for periodically correlated random processes characteristics obtained on the base of discrete time realization are given. Bias and variance formulae for the estimators ofmean and covariance Fourier coefficients are found. The conditions for discretization interval when aliasing effects do not occur are obtained. The dependences of estimator characteristics on discretization interval and realization length for modulated signals are analyzed.
Keywords: periodically correlated random processes (PCRP); mean; covariance; Fourier coefficients; discrete estimates; bias; variance; aliasing